2021
DOI: 10.1016/j.bja.2021.05.038
|View full text |Cite
|
Sign up to set email alerts
|

The central nervous system during lung injury and mechanical ventilation: a narrative review

Abstract: Mechanical ventilation induces a number of systemic responses for which the brain plays an essential role. During the last decade, substantial evidence has emerged showing that the brain modifies pulmonary responses to physical and biological stimuli by various mechanisms, including the modulation of neuroinflammatory reflexes and the onset of abnormal breathing patterns. Afferent signals and circulating factors from injured peripheral tissues, including the lung, can induce neuronal reprogramming, potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 131 publications
0
14
0
Order By: Relevance
“…In fact, it has been shown that critically ill patients are commonly admitted to the ICUs for MV [ 35 ]. Patient-ventilator interactions and the likelihood for developing acute lung injury is largely determined by the neural control of ventilation and the immune response, which could make patients susceptible to develop short- and long-term neuropsychological impairments, including delirium, sleep disturbances, persistent cognitive impairment, and post-traumatic stress disorder [ 36 ]. Although the interactions of the mechanically ventilated lung and CNS are complex and discussed in detail in the Pathophysiology Section, experimental and clinical studies suggest the existence of an interacting signalling.…”
Section: Clinical Cns Presentations In Ards Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been shown that critically ill patients are commonly admitted to the ICUs for MV [ 35 ]. Patient-ventilator interactions and the likelihood for developing acute lung injury is largely determined by the neural control of ventilation and the immune response, which could make patients susceptible to develop short- and long-term neuropsychological impairments, including delirium, sleep disturbances, persistent cognitive impairment, and post-traumatic stress disorder [ 36 ]. Although the interactions of the mechanically ventilated lung and CNS are complex and discussed in detail in the Pathophysiology Section, experimental and clinical studies suggest the existence of an interacting signalling.…”
Section: Clinical Cns Presentations In Ards Patientsmentioning
confidence: 99%
“…This interacting signalling could be due to a physiological mechanism, as for example the Hering–Breuer reflex. Another possible cause could be a pathological process, such as excessive alveolar stretch and over-distension, which could lead to maladaptive responses and contribute to the observed neurocognitive impairments and psychological alterations [ 36 , 37 ].…”
Section: Clinical Cns Presentations In Ards Patientsmentioning
confidence: 99%
“…There are several mechanisms that may lead to brain injury in critically ill patients [34]. The central nervous system (CNS) receives signals from neural afferences and circulating factors and cells.…”
Section: Molecular Mechanisms Of Cognitive Impairmentmentioning
confidence: 99%
“…And, in cases of severe acute lung injury, prolonged pronepositioning has been shown to significantly decrease 28-day and 90-day mortality (5). In mechanical ventilation-induced acute lung injury (VILI), brain dysfunction of the frontal cortex and hippocampus frequently occurs and clinically manifests as delirium (6)(7)(8). Delirium concomitant with mechanical ventilation and severe acute lung injury contributes to an accelerated trajectory of long-term cognitive decline, increased mortality, and prolonged length of hospital stay (7,8).…”
Section: Introductionmentioning
confidence: 99%